A multi-center prospective cohort study to evaluate the effect of differential pricing and health systems strengthening on access to medicines and management of hypertension and diabetes in Ghana: A study protocol - Mobula, Linda Meta (Gates Open Res, 2018)
Background: There is evidence to suggest that the prevalence of non-communicable diseases (NCDs), in particular cardiovascular diseases and diabetes, are being recognized as forming a substantial proportion of the burden of disease among populations in Low- and Middle-Income Countries (LMICs).  Access to treatment is likely a key barrier to the control and prevention of NCD outcomes.  Differential pricing, an approach used to price drugs based on the purchasing power of patients in different socioeconomic segments, has been shown to be beneficial and leads to improved access and affordability. Methods: This is a quasi-experimental study, with a pragmatic trial design, to be conducted over the course of three years. A mixed methods design will be used to evaluate the effects of health systems strengthening and differential pricing on the management of diabetes, hypertension and selected cancers in Ghana. A public private partnership was established between all sites that will receive multi-level interventions, including health systems strengthening  and access to medicines interventions. Study populations and sites: Study participants will include individuals with new or previously diagnosed hypertension and diabetes (n=3,300), who present to two major referral hospitals, Komfo Anokye Teaching Hospital and Tamale Teaching Hospital, as well as three district hospitals, namely Kings Medical Centre, Agogo Presbyterian District Hospital, and Atua Government Hospital. Discussion: The objective of this study aims to test approaches intended to improve access to drugs for the treatment of hypertension and diabetes, and improve disease control. Patients with these conditions will benefit from health systems strengthening interventions (education, counseling, improved management of disease), and increased access to innovative medicines via differential pricing. Pilot programs also will facilitate health system strengthening at the participating institutions, which includes training of clinicians and updating of guidelines and production of protocols for the treatment of diabetes, hypertension and cancer.